Financial Depth Measurements / Analytical Study in Selected Countries for the Period 1980-2008 - السعدي صبحي حسون (Journal of Economics and Administrative Sciences, 2011)
This research deals with the most important indicators used to measure the phenomenon of financial depth, beyond the traditional indicators, which are called quantitative indicators, which is shown to be inadequate to show the facts accurately, but it may come in the results of a counterfactual, although reliable in econometric studies done in this regard. Therefore, this research has sought to put forward alternative indicators, is the structural indicators, and financial prices, and availability of financial instruments, and cost of transactions concluded, in order to measure the phenomenon of financial depth. After using and analyzing data collected from countries the research sample, which included Japan, China and Iraq, which have been carefully selected to show the countries varied in the level of financial depth, in order to give the results of analytical variety explain all of reality, the time period 1980-2008, as averages, it was found that these standards alternative is better or closer to highlight the fact, it was found that Japan sits on the summit of the sample selected in terms of depth financial situation, followed by China with Iraq at the end. This basic finding of the research consistent with the hypothesis, which confirmed the importance of alternative measures to highlight the phenomenon of financial depth are more accurate and realistic.